Invasion Biology: Specific Problems and Possible Solutions - Courchamp, Franck; Fournier, Alice; Bellard, Céline; Bertelsmeier, Cleo; Bonnaud, Elsa; Jeschke, Jonathan M.; Russell, James C. (Trends in ecology & evolution (Amsterdam), 2017)
Biological invasions have been unambiguously shown to be one of the major global causes of biodiversity loss. Despite the magnitude of this threat and recent scientific advances, this field remains a regular target of criticism – from outright deniers of the threat to scientists questioning the utility of the discipline. This unique situation, combining internal strife and an unaware society, greatly hinders the progress of invasion biology. It is crucial to identify the specificities of this discipline that lead to such difficulties. We outline here 24 specificities and problems of this discipline and categorize them into four groups: understanding, alerting, supporting, and implementing the issues associated with invasive alien species, and we offer solutions to tackle these problems and push the field forward. Global analyses and recent syntheses confirm what the scientific community has claimed for decades: biological invasions cause major impacts and are a major cause of biodiversity loss worldwide. Despite increasing evidence, the importance of biological invasions is not generally acknowledged by the public, is not fully accepted by decision makers, and has even recently been increasingly disputed by some scientists. The mismatch between the urgency to deal with a major environmental issue and the little concern it receives from several key components of society needs to be recognized and the underlying reasons identified and addressed. Many reasons for this mismatch are not shared with other global change aspects and are specific to invasion biology; in particular, these include difficulties in raising awareness and understanding as well as in obtaining support for the implementation of conservation programs.